Review on Surfactant Flooding: Phase Behavior, Retention, IFT, and Field Applications - Kamal, Muhammad Shahzad; Hussein, Ibnelwaleed A; Sultan, Abdullah S (Energy & fuels, 2017)
Surfactant flooding is an important technique used in enhanced oil recovery to reduce the amount of oil in pore space of matrix rock. Surfactants are injected to mobilize residual oil by lowering the interfacial tension between oil and water and/or by the wettability alteration from oil-wet to water-wet. A large number of cationic, anionic, non-ionic, and amphoteric surfactants have been investigated on a laboratory scale under different conditions of temperature and salinity. Selection of the appropriate surfactant is a challenging task, and surfactants have to be evaluated by a series of screening techniques. Different types of surfactants along with their limitations are reviewed with particular emphasis on the phase behavior, adsorption, interfacial tension, and structure–property relationship. Factors affecting the phase behavior, interfacial tension, and wettability alteration are also discussed. Field applications of surfactants for chemical enhanced oil recovery in carbonate and sandstone reservoirs are also reviewed. Finally, some recent trends and future challenges in surfactant enhanced oil recovery are outlined. Field studies show that most of the surfactant flooding has been conducted in low-temperature and low-salinity sandstone reservoirs. However, high-temperature and high-salinity carbonate reservoirs are still challenging for implementation of surfactant flooding.